The Influence Of Inter-Ethnic Student Social Interaction At SMAN 4 Batam - Yona Martin; Agusti Efi (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2024)
This research is motivated by the existence of diverse ethnicities among students at SMA Negeri 4 Batam which have a positive or negative influence on students. This study aims to identify and analyze the impact of inter-ethnic student social interaction at SMAN 4 Batam and to explain the teacher's role in the social interaction of inter-ethnic students at SMAN 4 Batam. The approach used is qualitative with the type of case study research. The research informants were determined using a purposive sampling technique with the following criteria: Teachers, Students, and Student Assistants at SMAN 4 Batam. Data validity tests include credibility, transferability, dependability, and confirmability tests. Data analysis used the interactive analysis model Miles and Huberman. The results of the study show that the impact of inter-ethnic student social interaction is solidarity between the same ethnic groups, and stereotypes towards different ethnic groups. The teacher's role in inter-ethnic student interactions is to unite students in study groups, hold fashion show competitions, and encourage the use of Indonesian. This research is motivated by the existence of diverse ethnicities among students at SMA Negeri 4 Batam which have a positive or negative influence on students. This study aims to identify and analyze the impact of inter-ethnic student social interaction at SMAN 4 Batam and to explain the teacher's role in the social interaction of inter-ethnic students at SMAN 4 Batam. The approach used is qualitative with the type of case study research. The research informants were determined using a purposive sampling technique with the following criteria: Teachers, Students, and Student Assistants at SMAN 4 Batam. Data validity tests include credibility, transferability, dependability, and confirmability tests. Data analysis used the interactive analysis model Miles and Huberman. The results of the study show that the impact of inter-ethnic student social interaction is solidarity between the same ethnic groups, and stereotypes towards different ethnic groups. The teacher's role in inter-ethnic student interactions is to unite students in study groups, hold fashion show competitions, and encourage the use of Indonesian.